Պարչ-Նաումանի «Միջին Եվրոպայի» հայեցակարգերը - Սուքիասյան, Հայկ (YSU Journal of International Affairs, 2015)
The article studies the geopolitical concept of Middle Europe of Friedrich Naumann and Joseph Partch. This concept had a huge turnover in the German political circles during the First World War. In fact, this concept is characteristic for empires and for their passionate spirit, which describes the geostrategic position of Germany in the Middle Europe. Mitteleuropa – a concept of establishment of an empire due to occupied territories through the expansion of the concept, which will be created by the merger of Austro-Hungary with Germany.
Keywords: Middle Europe, Germany, geostrategy, territory, living space, expansion